2006
DOI: 10.4161/cbt.5.10.3454
|View full text |Cite
|
Sign up to set email alerts
|

Basal repression of BRCA1 by multiple E2Fs and pocket proteins at adjacent E2F sites

Abstract: The BRCA1 gene is rarely mutated in sporadic tumors, although numerous studies suggest that the expression of this critical tumor suppressor gene is frequently downregulated in tumors derived from a wide range of tissues. However, little is known regarding the mechanisms by which BRCA1 is transcriptionally regulated in human cells in vivo. We have shown recently that the tumor microenvironmental stress of hypoxia induces an E2F-dependent repression of BRCA1 in cancer cells. Here, we report that multiple E2Fs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 37 publications
2
41
0
Order By: Relevance
“…Definition of the relevant subset is ongoing, but at least one additional FA gene, FANCB, was noted by the DiMaio Laboratory as repressed in response to E2-mediated E7 repression in HeLa cells (Johung et al, 2007;supplementary data). Published reports on the E2F-dependent repression of Rad51 and BRCA1, specifically during hypoxia, (Oberley et al, 2003;Bindra and Glazer, 2006;Bindra et al, 2007), together with the repression of these two molecules in our microarray experiments (data not shown) and in Figure 2a, respectively, may imply coordination with a wider network of DNA repair pathways. With regard to human cancers exhibiting high E2F activity and rapid cell proliferation, the deregulation of individual, but not necessarily multiple, components of the system may be responsible for insufficient DNA repair, high mutational frequencies and carcinogenesis.…”
Section: Discussionmentioning
confidence: 90%
“…Definition of the relevant subset is ongoing, but at least one additional FA gene, FANCB, was noted by the DiMaio Laboratory as repressed in response to E2-mediated E7 repression in HeLa cells (Johung et al, 2007;supplementary data). Published reports on the E2F-dependent repression of Rad51 and BRCA1, specifically during hypoxia, (Oberley et al, 2003;Bindra and Glazer, 2006;Bindra et al, 2007), together with the repression of these two molecules in our microarray experiments (data not shown) and in Figure 2a, respectively, may imply coordination with a wider network of DNA repair pathways. With regard to human cancers exhibiting high E2F activity and rapid cell proliferation, the deregulation of individual, but not necessarily multiple, components of the system may be responsible for insufficient DNA repair, high mutational frequencies and carcinogenesis.…”
Section: Discussionmentioning
confidence: 90%
“…Previous work has shown that E7 prevents down-regulation of BRCA1 and RAD51 in hypoxia by disrupting p130/E2F4 binding to the respective promoters (11)(12)(13)(14)(15). E7 expression was found to confer resistance to PARP inhibition in hypoxic cells (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…In prior work, we found that hypoxia suppresses HDR in human cells via transcriptional down-regulation of BRCA1 and RAD51 (11)(12)(13)(14)(15). Hence, we hypothesized that cancer cells in hypoxia, with acquired deficiency in HDR, might have increased sensitivity to PARP inhibition.…”
mentioning
confidence: 99%
“…Furthermore, there is a paucity of evidence to link these BRCA1 regulators to defined BRCA1-dependent phenotypes. Metastasis-associated tumor antigen 1 (MTA1) has been implicated in the transcriptional repression of BRCA1 and in abnormal centrosome number and chromosomal instability (30), and E2F4 and the pocket proteins p130/p107 bind the BRCA1 promoter and repress its basal transcription, thereby regulating cell growth (97). In these studies, we demonstrate that HOXA9 directly and positively modulates BRCA1 transcription, thereby restricting the abnormal growth, survival, and stress response of breast cancer cells and nonmalignant MECs in culture and in vivo.…”
Section: Discussionmentioning
confidence: 99%